Quantitative and Qualitative Approaches in Managing Human Resource Development in Enterprises - Buzko, Iryna; Dyachenko, Yuriy; Ovcharenko, Ievgen; Klius, Yuliia (International Journal of Engineering and Technology, 2018)
The paper proposes comparing the existing and the required level of competence of the employee as a tool for determining the qualitative and quantitative parameters of personnel training. To implement this comparison, in accordance with official requirements, the human capital required for the performance of official duties as an employee's quality, which acquires value in the process of attracting to industrial relations, is calculated. Qualitative and quantitative parameters of personnel training are determined on the basis of calculation of the difference between necessary and existing competence taking into account financial possibilities of the enterprise. According to the results of calculating the available human capital, which a certain employee owns, and comparing it with the necessary one, the content (according to the type of insufficient capital) and the amount (by difference between the existing and the required level) of training, which should bring the available human capital of the employee in accordance with the required one. Formation of the content of the training is based on the definition of individual assets of human capital, which depend on the requirements for the competence of the employee and can be changed through training.Â